A national strategy for teaching excellence – one university at a time - Chalmers, D.; Tucker, Beatrice (Routledge, 2018)
This chapter outlines a case study on the development of a national strategy for teaching excellence and its implementation in over two thirds of Australian univer-sities. This has resulted in a growing consensus on teaching criteria and performance expectations for higher education teachers at different promotional levels.